Administrative Violations And Legal Disputes In The Management Of Bengkok Land By The Village Government - Fajri, Naura Nurul; Azizah, Aulia Nur; Pamungkas, Andhika Ivan Putra (MIH FH UNSOED, 2025)
Land bengkok is land that is controlled by the state and can be utilized by those who want to devote themselves as administrators in a village as a form of appreciation. The bengkok land is managed by the village head, village secretary, and village officials. However, in its management, it often causes conflicts related to the right to use and land ownership. This research examines the management of bengkok land related to the village head's decree on the contract of bengkok land that exceeds his term of office. The purpose of this study is to determine the juridical review of the village head's decision on the contract of bengkok land based on Pemendagri No. 1 of 2016 and Paremono village regulations related to village assets. The method used in this research is a qualitative empirical research method, which is carried out by means of interpretation of legal materials that have been collected and reinforced by direct statements from village officials (community). The results of this study conclude that one of the village assets is a village asset whose management needs juridical protection, the village head concerned meets the elements of a state administrative dispute based on Article 12 Permendagri Number 1 of 2016 concerning the management of village assets which exceeds the length of the lease while the maximum rental limit is 3 years and Article 10.